Stable diesel microemulsion using diammonium ionic liquids and their effects on fuel properties, particle size characteristics and combustion calculations - H. A. El Nagy; Mahmoud Abd El-Aziz Mohamed (Scientific Reports, 2024)
Abstract Ecofriendly and stable Fuel Microemulsions based on renewable components were prepared through solubilizing ethanol in diesel and waste cooking oil blend (4:1). New diquaternary ammonium ionic liquids (3a & 3b) were synthesized through a quaternization reaction of the synthesized dihaloester with diethyl ethanolamine tridecantrioate and triethyl amine tridecantrioate, respectively. The chemical structures were elucidated by NMR spectroscopy. It was observed from DLS analyses that the ethanol particles in all samples have sizes between 4.77 to 11.22 nm. The distribution becomes narrower with the decrease in the ionic liquid concentrations. The fuel properties fall within the ASTM D975 acceptable specifications and are close to the neat diesel properties. The Cetane index were 53 and 53.5, heating values were 38.5 and 38.5 MJ/kg, viscosities were 2.91 and 2.98 mm2/s, densities were 8.26 and 8.29 g/mL and flash points were 49 °C and 48 °C for 3a1 and 3b1 microemulsions, respectively. The particle sizes of samples were examined by DLS for 160 days and they were significantly stable. The amount of ethanol solubilized increases with the increase in the amount of the synthesized ionic liquids and cosurfactant. The combustion calculations pointed out that the microemulsions 3a1 and 3b1 need 13.07 kg air/kg fuel and 12.79 kg air/kg fuel, respectively, which are less than the air required to combust the pure diesel. According to theoretical combustion, using ionic liquids saves the air consumption required for combustion and reduces the quantities of combustion products. The prepared microemulsions were successfully used as a diesel substitute due to their improved combustion properties than pure diesel and low pollution levels.